The Effect of Information Management Capability, Collaboration, and Supply Chain Resilience on Company Performance - James Korompis; Zeplin Jiwa Husada Tarigan; Oviliani Yenty Yuliana (Master of Management, School of Business and Management, Petra Christian University, 2022)
A covid-19 pandemic is a significant event that causes supply chain disruption in Indonesia. As a result, the manufacturing sector experienced a significant decline which is indicated by the greatly decreasing Purchasing Manager Index (PMI) in April and May 2020. Therefore, supply chain resilience (SCR) becomes essential for a company to minimize risk, reduce negative impact, and quickly adapt to the business condition. This research aims to analyse the relationship between variables that can increase SCR, namely information management capability (IMC) and collaboration, and the relationship between SCR and company performance. This research was conducted by collecting primary data using questionnaires and analysing the relationship among variables using the PLS-SEM method. This research indicates that IMC and collaboration significantly affect SCR. SCR also has a significant effect on company performance. However, IMC does not significantly impact company performance, while collaboration significantly affects company performance. This research also indicates that collaboration mediates the relationship between IMC toward company performance.